L’industrie de l’assurance au Québec : bilan et prospective - Bouchard, Jean-Marie (Assurances)

(untitled) (HEC Montréal, 1992)
We are pleased to publish a general overview and some reflections on the orientation of the insurance industry by the lnspector General of Financial Institutions. This article focuses on the Quebec reform of financial institutions and on the regulatory role and responsabilities of the Inspector General. It also highlights the characteristics of the Quebec insurance industry such as deregulation, market statistics and new trends, the challenges of the global market and the emergence of new conglomerates in the final decade of this century.